TAG: Gradient Attack on Transformer-based Language Models - Deng, Jieren; Wang, Yijue; Li, Ji; Shang, Chao; Liu, Hang; Rajasekaran, Sanguthevar; Ding, Caiwen (2021 Empirical Methods in Natural Language Processing, 2021)
Although federated learning has increasingly gained attention in terms of effectively utilizing local devices for data privacy enhancement, recent studies show that publicly shared gradients in the training process can reveal the private training images (gradient leakage) to a third-party in computer vision. We have, however, no systematic understanding of the gradient leakage mechanism on the Transformer based language models. In this paper, as the first attempt, we formulate the gradient attack problem on the Transformer-based language models and propose a gradient attack algorithm, TAG, to reconstruct the local training data. We develop a set of metrics to evaluate the effectiveness of the proposed attack algorithm quantitatively. Experimental results on Transformer, TinyBERT_[4], TinyBERT_[6], BERT_[BASE], and BERT_[LARGE] using GLUE benchmark show that TAG works well on more weight distributions in reconstructing training data and achieves 1.5× recover rate and 2.5× ROUGE-2 over prior methods without the need of ground truth label. TAG can obtain up to 90% data by attacking gradients in CoLA dataset. In addition, TAG has a stronger adversary on large models, small dictionary size, and small input length. We hope the proposed TAG will shed some light on the privacy leakage problem in Transformer-based NLP models.